Handshake, No. 3 (October 2011) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: integrated health systems: Lesothos pioneering model; access to healthcare for the poor: lessons from Ghana, India, and Mexico; and cost efficiency: Singapores secret to healthcare.